Evidentiality and epistemological stance : narrative retelling - Mushin, Ilana (Pragmatics & beyond, 2001)
This book explores the discourse pragmatics of reportive evidentiality in Macedonian, Japanese and English through an empirical study of evidential strategies in narrative retelling. The patterns of evidential use (and non-use) found in these languages are attributed to contextual, cultural and grammatical factors that motivate the adoption of an 'epistemological stance' -- a concept that owes much to recent trends in Cognitive Linguistics. The patterns of evidential strategies found in the three languages provide a fine illustration of the balancing act between speakers' expressions of their.